The Resistance and Negotiation of Religious Culture-Specific Terms in Translating Novel Cantik Itu Luka from Indonesian to French - Arrasyid, Noor Diana; Sajarwa, Sajarwa (PAROLE: Journal of Linguistics and Education, 2023)
The cultural differences between source language and target language give rise to the resistance and negotiation in translation. This study aims to observe the resistance and negotiation patterns that arise in religious cultural terms translation. This study uses a descriptive qualitative approach to analyze the source text in Indonesian and the target text in French and identify the resistance and negotiation emergence in the translation outcome. The results show that the resistance emergence frequency is strongly relates to religious figures and religious groups’ translation. The resistance also arises when the translator only provides a footnote on a term. On the other hand, negotiation often arises in translations that correspond to religious artifacts and moral aspects. We concluded that resistance emerges in various cultural terms translation which the references are general in religious culture-specific terms. Conversely, cultural terms translation that have specific and diverse references tend to be negotiable. The existence of specifications and diverse of meaning of a religious culture-specific terms will make their meaning fading, particularly for target text readers.